2022
DOI: 10.3389/fnmol.2022.822863
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights of Unfolding of N-Terminal Domain of TDP-43 Reveal the Conformational Heterogeneity in the Unfolding Pathway

Abstract: TDP-43 proteinopathies is a disease hallmark that characterizes amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). The N-terminal domain of TDP-43 (NTD) is important to both TDP-43 physiology and TDP-43 proteinopathy. However, its folding and dimerization process is still poorly characterized. In the present study, we have investigated the folding/unfolding of NTD employing all-atom molecular dynamics (MD) simulations in 8 M dimethylsulfoxide (DMSO) at high temperatures. The MD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The interplay between TDP‐43 dimerization and aggregation was investigated using equilibrium molecular dynamics (MD) simulations. [ 25 ] The NTD can sample several conformations en route to the fully folded state, and it has been hypothesized that these partially folded forms of the domain mediate aggregation rather than proper dimerization. Interestingly, the earliest structure of the NTD featured the monomeric form after exposure to denaturing conditions.…”
Section: Tdp‐43 Ntd Dimerization and Aggregationmentioning
confidence: 99%
“…The interplay between TDP‐43 dimerization and aggregation was investigated using equilibrium molecular dynamics (MD) simulations. [ 25 ] The NTD can sample several conformations en route to the fully folded state, and it has been hypothesized that these partially folded forms of the domain mediate aggregation rather than proper dimerization. Interestingly, the earliest structure of the NTD featured the monomeric form after exposure to denaturing conditions.…”
Section: Tdp‐43 Ntd Dimerization and Aggregationmentioning
confidence: 99%
“…In both the complexes, the Rg value is 1.5 nm, suggesting that the protein structure occupies a region of space. A relatively constant Rg value suggests that the structure remains stable and relatively compact structure [82]. Hydrogen bonding is essential for maintaining the structural stability of proteins in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have hitherto been widely utilized in the study of peptide folding and aggregation. The investigations of the aggregation process and structural characteristics of TDP-43 fragments using MD simulations have emerged in recent years. For example, Imtaiyaz Hassan and co-workers unraveled the fact that the 247 DLIIKGIS 254 fragment in the RRM2 domain of TDP-43 has the ability to self-aggregate and transit into β-sheet-rich structures by utilizing all-atom MD simulations . Lynn et al demonstrated that RRM1/RRM2 exhibit different structural stabilities by performing MD simulations at two different temperatures .…”
Section: Introductionmentioning
confidence: 99%